Pengaruh Persepsi Generasi Z Terhadap Pilihan Karir pada Mahasiswa Program Studi Manajemen Universitas Pamulang - Eka Nurkhasannah,; Shafa Anggita Putri, (Journal of Management and Creative Business, 2025)
This study aims to analyze the influence of Generation Z perceptions on career choices among students of the Management Study Program at Pamulang University. With the background that Generation Z has unique characteristics in choosing a career, this study explores how their perceptions of various factors—such as company values, career development, and life balance—influence their career decisions. The research method used is a quantitative approach with data collection through questionnaires distributed to active students in the study program. Data analysis was carried out using linear regression to identify the relationship between perception variables and career choices. The results of the study indicate that positive perceptions of career development and company values ​​contribute significantly to determining students' career choices. These findings indicate the importance of understanding Generation Z's perspectives in the context of the ever-changing dynamics of the world of work, as well as implications for educational institutions and companies in designing relevant programs to attract and retain young talent.